Lean body mass and the cardiorespiratory phenotype: An ethnic‐specific relationship in Hans Chinese women and men - Meihan Guo; Candela Diaz‐Canestro; Nicola Riccardo Pugliese; Francesco Paneni; David Montero (Wiley, 2024)
Abstract Background Lean body mass (LBM) and the functional capacity of cardiovascular (CV) and respiratory systems constitute a female‐specific relationship in European-American individuals. Whether this recent finding be extrapolated to the world's largest ethnic group, that is, Hans Chinese (HC, a population characterized by low LBM), is unknown. Methods Healthy HC adults (n = 144, 50% ♀) closely matched by sex, age and physical activity were included. Total and regional (leg, arm and trunk) LBM and body composition were measured via dual‐energy X‐ray absorptiometry. Cardiac structure, stiffness, central/peripheral haemodynamics and peak O2 consumption (VO2peak) were assessed via transthoracic echocardiography and pulmonary gas analyses at rest and during exercise up to peak effort. Regression analyses determined the sex‐specific relationship of LBM with cardiac and aerobic phenotypes. Results Total and regional LBM were lower and body fat percentage higher in women compared with men (P < 0.001). In both sexes, total LBM positively associated with left ventricular (LV) mass and peak volumes (r ≥ 0.33, P ≤ 0.005) and negatively with LV end‐systolic and central arterial stiffness (r ≥ −0.34, P ≤ 0.004). Total LBM strongly associated with VO2peak (r ≥ 0.60, P < 0.001) and peak cardiac output (r ≥ 0.40, P < 0.001) in women and men. Among regional LBM, leg LBM prominently associated with the arterio‐venous O2 difference at peak exercise in both sexes (r ≥ 0.43, P < 0.001). Adjustment by adiposity or CV risk factors did not modify the results. Conclusions LBM independently determines internal cardiac dimensions, ventricular mass, distensibility and the capacity to deliver and consume O2 in HC adults irrespective of sex.